2021
DOI: 10.1017/ice.2021.192
|View full text |Cite
|
Sign up to set email alerts
|

Who’s vaccinated? A closer look at healthcare workers’ coronavirus disease 2019 (COVID-19) COVID-19 vaccine hesitancy and demographics

Abstract: Objective: To compare COVID-19 vaccine hesitancy among hospital employees by demographics. Methods: Our institution has offered an mRNA COVID-19 vaccine to all employees since January 2021. We collected data on vaccination rates among hospital employees and looked for differences in demographic groups to determine in which groups vaccine hesitancy is the highest. Those who received at least one dose of vaccine were considered “vaccinated” for this study. Results: There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…We found that participants offer a wide variety of reasons why they might not become vaccinated. Although previous research has emphasized the prevalence of myths about the vaccine (Allington et al, 2021a;El-Elimat et al, 2021;García-Montero et al, 2021;Hornsey et al, 2021;Kumari et al, 2021;Montalti et al, 2021;Ullah et al, 2021) or on overcoming exaggerated concerns about safety and side effects (Levin-Zamir, 2020; Thaker, 2021) as key message Fossen et al, 2021;Green et al, 2021;Peteet et al, 2021). Moreover, the wide dispersion of reasons offered indicates that a single-message intervention distributed through mass media is unlikely to succeed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that participants offer a wide variety of reasons why they might not become vaccinated. Although previous research has emphasized the prevalence of myths about the vaccine (Allington et al, 2021a;El-Elimat et al, 2021;García-Montero et al, 2021;Hornsey et al, 2021;Kumari et al, 2021;Montalti et al, 2021;Ullah et al, 2021) or on overcoming exaggerated concerns about safety and side effects (Levin-Zamir, 2020; Thaker, 2021) as key message Fossen et al, 2021;Green et al, 2021;Peteet et al, 2021). Moreover, the wide dispersion of reasons offered indicates that a single-message intervention distributed through mass media is unlikely to succeed.…”
Section: Discussionmentioning
confidence: 99%
“…Even in environments, such as employees within the same clinic, where everyone has equal access to COVID-19 vaccines, perceptions of these vaccines still remain an important explanation for why some people choose to get vaccinated and others do not (Dzieciolowska et al, 2021;Fossen et al, 2021). COVID-19 vaccine hesitancy is often attributed to a person's belief in myths and disinformation (Allington et al, 2021a;El-Elimat et al, 2021;García-Montero et al, 2021;Hornsey et al, 2021;Kumari et al, 2021;Montalti et al, 2021;Ullah et al, 2021).…”
Section: Reasons For Covid-19 Vaccine Hesitancymentioning
confidence: 99%
See 1 more Smart Citation
“…As noted with regard to the “3 C’s” model of vaccine hesitancy, convenience is an important factor in increasing vaccine uptake (MacDonald et al, 2015 ). Fossen et al ( 2021 ) determined that healthcare personnel working in clinical areas with the most convenient access to vaccines were more likely to get vaccinated than other types of healthcare professions (for similar results, see King et al, 2021 ).…”
Section: Introductionmentioning
confidence: 90%
“…As employer mandates for vaccination become an increasingly discussed, yet highly politicized, tool for accomplishing herd immunity to COVID-19, understanding how workplace conditions may influence vaccine hesitancy is critical. Though the extant literature on the relationship between occupation and vaccine hesitancy is limited, emerging findings suggest that variation in vaccine intent between occupational groups is significant (Fossen et al, 2021 ; King et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%